Bio-based polyurethane hot melt adhesive and preparation process thereof

By combining modified carbon nanotubes and UV absorbers, the bonding performance and aging resistance of bio-based polyurethane hot melt adhesives are enhanced, solving the resource dependence and performance deficiencies of traditional polyurethane hot melt adhesives and achieving environmentally friendly and efficient adhesive applications.

CN120665554APending Publication Date: 2025-09-19GUANGDONG SANQI CHEM TECH CO LTD

Patent Information

Application Number
CN202510209625.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Traditional polyurethane hot melt adhesives rely on petroleum-based raw materials, which have limited resources and are environmentally unfriendly. Their mechanical properties and aging resistance are insufficient, affecting their service life and quality.

Method used

Modified carbon nanotubes are prepared by modifying graphene oxide with a silane coupling agent and acid-treating carbon nanotubes. Modified carbon nanotubes, ultraviolet absorbers and antioxidants are added to bio-based polyurethane hot melt adhesive. Through chemical reactions, the three-dimensional spatial structure of the carbon nanotubes is expanded and the surface roughness is increased, thereby enhancing the bonding performance and aging resistance.

Benefits of technology

The prepared bio-based polyurethane hot melt adhesive has excellent bonding and mechanical properties, significantly extends its service life and ensures quality. It is suitable for use in automotive manufacturing, home appliances, electronic products, plastics and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005285622790000101
    Figure BDA0005285622790000101
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a bio-based polyurethane hot melt adhesive and a preparation process thereof. The bio-based polyurethane hot melt adhesive is prepared from the following raw materials in parts by weight: 30 to 40 parts of bio-based polyester glycol, 60 to 80 parts of bio-based polyether polyol, 25 to 35 parts of acrylic resin, 40 to 60 parts of isophorone diisocyanate, 3 to 5 parts of bisphenol A epoxy resin E-44, 3 to 5 parts of 1, 3-butanediol, 1, 3-butanediol and 1, 3-butanediol. The coating is prepared from the following raw materials in parts by weight: 1-2 parts of 1, 4-butanediol, 0.2-0.6 part of dibutyltin dilaurate, 0.6-1.0 part of 3-aminopropyltriethoxysilane, 3-5 parts of modified carbon nanotubes, 2-4 parts of a curing agent, 1-1.5 parts of an ultraviolet absorbent and 0.8-1.2 parts of an antioxidant. The bio-based polyurethane hot melt adhesive prepared by the invention not only has better adhesive property, but also has excellent mechanical property and aging resistance, and the quality of the bio-based polyurethane hot melt adhesive is ensured while the service life of the bio-based polyurethane hot melt adhesive is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a bio-based polyurethane hot melt adhesive and a preparation process thereof. Background Art

[0002] Polyurethane hot melt adhesive, also known as hot melt polyurethane adhesive, refers to a type of hot melt adhesive made from polyurethane resin as the main material and various additives. Compared with EVA hot melt adhesive, polyurethane hot melt adhesive has advantages such as good low-temperature toughness, excellent adhesion, high strength, and high polarity. It is widely used in many fields such as automobile manufacturing, home appliances, electronic products, plastics, and textiles. As people's attention to environmental protection and sustainable development continues to increase, the research and development and application of bio-based materials have received widespread attention. As an important adhesive, polyurethane hot melt adhesive has a wide range of applications in many fields, but traditional polyurethane hot melt adhesives mostly rely on petroleum-based raw materials, and have problems such as limited resources and environmental friendliness. Therefore, it is of great significance to develop a bio-based polyurethane hot melt adhesive with excellent performance and environmental friendliness.

[0003] Patent document CN202111155909.0 discloses a bio-based reactive polyurethane hot melt adhesive and its preparation method. The bio-based reactive polyurethane hot melt adhesive comprises the following components and parts by weight: 40-80 parts of bio-based polyester diol; 15-35 parts of polyether polyol; 10-25 parts of polyisocyanate; 0.1-2 parts of antioxidant; 0.1-2 parts of first catalyst; 0-35 parts of thermoplastic resin; 0-5 parts of silane coupling agent; and 0-10 parts of auxiliary agent. Although the polyurethane hot melt adhesive prepared in this patent document has the advantages of being environmentally friendly and having good bonding strength, its mechanical properties and aging resistance are relatively insufficient, which not only shortens its service life to a certain extent but also affects its quality.

[0004] Therefore, the present invention provides a bio-based polyurethane hot melt adhesive and a preparation process thereof to solve the above-mentioned technical problems! Summary of the Invention

[0005] The purpose of the present invention is to provide a bio-based polyurethane hot melt adhesive and a preparation process thereof. The prepared bio-based polyurethane hot melt adhesive not only has good bonding properties, but also has excellent mechanical properties and aging resistance, which effectively extends its service life while also ensuring its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A bio-based polyurethane hot melt adhesive is composed of the following raw materials in parts by weight: 30-40 parts of bio-based polyester diol, 60-80 parts of bio-based polyether polyol, 25-35 parts of acrylic resin, 40-60 parts of isophorone diisocyanate, 3-5 parts of bisphenol A epoxy resin E-44, 3-5 parts of 1,4-butanediol, 0.2-0.6 parts of dibutyltin dilaurate, 0.6-1.0 parts of 3-aminopropyltriethoxysilane, 3-5 parts of modified carbon nanotubes, 2-4 parts of curing agent, 1-1.5 parts of ultraviolet absorber and 0.8-1.2 parts of antioxidant.

[0008] Furthermore, the preparation method of the modified carbon nanotubes comprises the following steps:

[0009] Step 1: adding pretreated carbon nanotubes to N,N-dimethylformamide at a ratio of 15 to 35 g / L, adding modified graphene oxide with a mass of 50 to 80% of the pretreated carbon nanotubes, ultrasonically dispersing for 1 to 2 hours, and then stirring at a temperature of 75 to 85° C. for 10 to 15 hours; after the reaction is completed, reflux reaction for 8 to 12 hours; cooling the reaction product to room temperature, and filtering, washing with water, and freeze-drying in sequence, and storing the obtained solid material for future use;

[0010] Step 2: The solid material is uniformly dispersed in a 90-95 wt% ethanol aqueous solution at a solid-liquid ratio of 30-80 g / L. A tetrabutyl titanate ethanol dispersion having a volume of 10-20% of the ethanol aqueous solution and a volume concentration of 30-50% is added while stirring. The mixture is stirred until a large amount of white precipitate is generated. The resulting product components are allowed to stand, and then filtered and dried in sequence to obtain modified carbon nanotubes.

[0011] Furthermore, the preparation method of the modified graphene oxide is as follows: graphene oxide is added to deionized water at a solid-liquid ratio of 10 to 30 g / L, ultrasonically dispersed and then the pH is adjusted to 4.5 to 5.0; then, an ethanol solution of a silane coupling agent KH-560 having a volume of 20 to 30% and a concentration of 5 to 8 wt% is added to the obtained aqueous dispersion of graphene oxide, mixed and stirred evenly, and then kept warm at a temperature of 60 to 70° C. for 8 to 12 hours; after the reaction is completed, the resultant components are naturally cooled to room temperature, filtered, and the filter cake is washed with deionized water until neutral, and then dried to obtain the modified graphene oxide.

[0012] Furthermore, the preparation method of the pretreated carbon nanotubes is: ultrasonically dispersing the carboxylated carbon nanotubes in thionyl chloride at a solid-liquid ratio of 20 to 50 g / L, and then reacting at a temperature of 65 to 85° C. for 15 to 25 hours; after the reaction is completed, naturally cooling the resulting product components to room temperature, and then filtering, washing and vacuum drying in sequence to obtain the pretreated carbon nanotubes.

[0013] Furthermore, the preparation method of the carboxylated carbon nanotubes is as follows: carbon nanotubes are added to a mixed acid solution at a dosage ratio of 10 to 30 g / L, ultrasonically dispersed for 5 to 8 hours, and then allowed to stand and centrifuged in sequence; the precipitate is then washed with deionized water until it is neutral, and then vacuum dried to obtain the carboxylated carbon nanotubes; wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.

[0014] Furthermore, the bio-based polyester diol is poly(1,3-propylene adipate) diol, and its relative molecular mass is 1000-2000.

[0015] Furthermore, the bio-based polyether polyol has a hydroxyl value of 55 to 60 mgKOH / g and a functionality of 3, and is prepared by ring-opening polymerization with propylene oxide using castor oil as an initiator and KOH as a catalyst.

[0016] Furthermore, the antioxidant is selected from any one of antioxidant 1076, antioxidant 1035, antioxidant 245, and antioxidant 1010.

[0017] Furthermore, the ultraviolet absorber is selected from any one of ultraviolet absorber UV-327, ultraviolet absorber UV-531, and ultraviolet absorber UV-1130.

[0018] A preparation process of a bio-based polyurethane hot melt adhesive comprises the following steps:

[0019] The first step is to put bio-based polyester diol, bio-based polyether polyol, acrylic resin and 1,4-butanediol into a reactor, raise the reactor temperature to 110-130°C, mix and stir evenly, and then dehydrate under vacuum conditions for 2-3 hours; after dehydration, cool to 50-70°C, then add isophorone diisocyanate under nitrogen protection, mix and stir evenly, and then keep stirring at 110-130°C for 2-3 hours;

[0020] Step 2: After the reaction is completed, add dibutyltin dilaurate under the protection of nitrogen, evenly disperse it, and then keep it warm at 90-120°C for 40-60 minutes. After the reaction is completed, add the remaining raw materials into the reactor, keep it warm and stir for 50-80 minutes, and then degas for 10-20 minutes. After filtering, discharging, and vacuum sealing packaging, the bio-based polyurethane hot melt adhesive is obtained.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention first modifies graphene oxide using the silane coupling agent KH-560 to produce modified graphene oxide. Simultaneously, carbon nanotubes are immersed in a mixed acid solution consisting of concentrated sulfuric acid and concentrated nitric acid to acidify the carbon nanotubes and produce carboxylated carbon nanotubes. The resulting carboxylated carbon nanotubes are then ultrasonically dispersed in thionyl chloride, and a chemical reaction is performed to produce pretreated carbon nanotubes.

[0023] Pretreated carbon nanotubes are placed in N,N-dimethylformamide and modified graphene oxide is added. After ultrasonic dispersion, the mixture is stirred and then refluxed. This chemical reaction between the modified graphene oxide and the pretreated carbon nanotubes forms bonds, effectively expanding the three-dimensional structure of the carbon nanotubes and increasing their branching. The resulting solid material is then placed in an ethanol-water solution and a tetrabutyl titanate ethanol dispersion is added. The stirring reaction deposits a dense nano-titanium dioxide film on the surface of the solid material, increasing the surface roughness, significantly increasing the contact area between the modified carbon nanotubes and the polyurethane hot-melt adhesive matrix, and enhancing the friction between the two. The synergistic effect of graphene oxide and carbon nanotubes results in the prepared polyurethane hot-melt adhesive exhibiting excellent bonding and mechanical properties. Furthermore, the interaction between the titanium dioxide film on the solid material's surface, the antioxidant, and the UV absorber further improves the polyurethane hot-melt adhesive's aging resistance, effectively extending its service life while maintaining its quality. DETAILED DESCRIPTION

[0024] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0025] Example 1

[0026] A bio-based polyurethane hot melt adhesive, comprising the following raw materials in parts by weight: 30 parts of bio-based polyester diol, 60 parts of bio-based polyether polyol, 25 parts of acrylic resin, 40 parts of isophorone diisocyanate, 3 parts of bisphenol A epoxy resin E-44, 3 parts of 1,4-butanediol, 0.2 parts of dibutyltin dilaurate, 0.6 parts of 3-aminopropyltriethoxysilane, 3 parts of modified carbon nanotubes, 2 parts of curing agent, 1 part of ultraviolet absorber UV-327, and 0.8 parts of antioxidant 1076;

[0027] Among them, the bio-based polyester diol uses poly 1,3-propylene adipate diol with a relative molecular mass of 1000; the bio-based polyether polyol has a hydroxyl value of 55mgKOH / g and a functionality of 3, and is prepared by ring-opening polymerization with propylene oxide using castor oil as an initiator and KOH as a catalyst; the curing agent uses ALT-101 curing agent from the European CARBON Chemical Institute; the acrylic resin uses Japan Mitsubishi BR-113 acrylic resin

[0028] The preparation method of modified carbon nanotubes comprises the following steps:

[0029] Step 1: adding pretreated carbon nanotubes to N,N-dimethylformamide at a ratio of 15 g / L, adding modified graphene oxide in an amount of 50% of the mass of the pretreated carbon nanotubes, ultrasonically dispersing for 1 hour, and then stirring at 75° C. for 10 hours; after the reaction is completed, reflux reaction is continued for 8 hours; the reaction product is cooled to room temperature, and filtered, washed with water, and freeze-dried in sequence, and the obtained solid material is stored for future use;

[0030] Step 2: The solid material is uniformly dispersed in a 90 wt% ethanol aqueous solution at a solid-liquid ratio of 30 g / L. A 50% volume concentration of tetrabutyl titanate in ethanol is added while stirring. The mixture is stirred until a large amount of white precipitate is generated. The resulting product components are allowed to stand, and then filtered and dried in sequence to obtain modified carbon nanotubes.

[0031] The preparation method of modified graphene oxide comprises the following steps: adding graphene oxide into deionized water at a solid-liquid ratio of 10 g / L, uniformly dispersing the graphene oxide by ultrasonication, and adjusting the pH to 4.5; then adding an ethanol solution of a silane coupling agent KH-560 having a volume of 20% and a concentration of 5 wt% to the obtained graphene oxide aqueous phase dispersion, mixing and stirring the mixture, and then heat-retaining the mixture at a temperature of 60° C. for 8 hours; after the reaction is completed, naturally cooling the resultant components to room temperature, filtering the resultant components, washing the filter cake with deionized water until the filter cake is neutral, and then drying the resultant components to obtain the modified graphene oxide.

[0032] The preparation method of pretreated carbon nanotubes is as follows: carboxylated carbon nanotubes are ultrasonically dispersed in thionyl chloride at a solid-liquid ratio of 20 g / L, and then reacted at a temperature of 65°C for 15 hours; after the reaction is completed, the resulting product components are naturally cooled to room temperature, and then filtered, washed and vacuum dried in sequence to obtain pretreated carbon nanotubes.

[0033] The preparation method of carboxylated carbon nanotubes is as follows: carbon nanotubes with a diameter of 20 nm and a length of 10 μm are added to a mixed acid solution at a dosage ratio of 10 g / L, and then ultrasonically dispersed for 5 hours, followed by standing and centrifugal separation; the precipitate is then washed with deionized water until neutral, and then vacuum dried to obtain the carboxylated carbon nanotubes; wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.

[0034] A preparation process of a bio-based polyurethane hot melt adhesive comprises the following steps:

[0035] In the first step, bio-based polyester diol, bio-based polyether polyol, acrylic resin and 1,4-butanediol were added to a reactor, the reactor temperature was raised to 110°C, mixed and stirred evenly, and then dehydrated under vacuum conditions for 2 hours; after dehydration, the temperature was lowered to 50°C, and then isophorone diisocyanate was added under nitrogen protection, mixed and stirred evenly, and then reacted at a temperature of 110°C with stirring for 2 hours;

[0036] Step 2: After the reaction is completed, add dibutyltin dilaurate under the protection of nitrogen, evenly disperse it and keep it warm at 90°C for 40 minutes; after the reaction is completed, add the remaining raw materials into the reactor, keep it warm and stir for 50 minutes, and then degas for 10 minutes. After filtering, discharging, and vacuum sealing packaging, the bio-based polyurethane hot melt adhesive is obtained.

[0037] Example 2

[0038] The preparation process of a bio-based polyurethane hot melt adhesive provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the bio-based polyurethane hot melt adhesive and the preparation method of the modified carbon nanotubes are not exactly the same. The specific composition of the bio-based polyurethane hot melt adhesive and the preparation method of the modified carbon nanotubes in this embodiment are as follows:

[0039] A bio-based polyurethane hot melt adhesive, comprising the following raw materials in parts by weight: 35 parts of bio-based polyester diol, 70 parts of bio-based polyether polyol, 30 parts of acrylic resin, 50 parts of isophorone diisocyanate, 4 parts of bisphenol A epoxy resin E-44, 5 parts of 1,4-butanediol, 0.4 parts of dibutyltin dilaurate, 0.8 parts of 3-aminopropyltriethoxysilane, 4 parts of modified carbon nanotubes, 3 parts of curing agent, 1.2 parts of ultraviolet absorber UV-531, and 1 part of antioxidant 1035;

[0040] Among them, the bio-based polyester diol is poly(1,3-propylene adipate) diol, and its relative molecular mass is 1000; the bio-based polyether polyol has a hydroxyl value of 60 mgKOH / g and a functionality of 3. It is prepared by ring-opening polymerization with propylene oxide using castor oil as an initiator and KOH as a catalyst.

[0041] The preparation method of modified carbon nanotubes comprises the following steps:

[0042] Step 1: adding pretreated carbon nanotubes to N,N-dimethylformamide at a ratio of 25 g / L, adding modified graphene oxide with a mass of 60% of the pretreated carbon nanotubes, ultrasonically dispersing for 2 hours, and then stirring at 80° C. for 15 hours; after the reaction is completed, reflux reaction for 10 hours; cooling the reaction product to room temperature, and filtering, washing with water, and freeze-drying in sequence, and storing the obtained solid material for future use;

[0043] Step 2: The solid material is uniformly dispersed in a 90 wt% ethanol aqueous solution at a solid-liquid ratio of 50 g / L. A 40% volume concentration of tetrabutyl titanate ethanol dispersion with a volume ratio of 15% of the ethanol aqueous solution is added while stirring. The mixture is stirred until a large amount of white precipitate is generated. The resulting product components are allowed to stand, and then filtered and dried in sequence to obtain modified carbon nanotubes.

[0044] The preparation method of modified graphene oxide comprises the following steps: adding graphene oxide into deionized water at a solid-liquid ratio of 20 g / L, uniformly dispersing the graphene oxide by ultrasonication, and adjusting the pH to 4.5; then adding an ethanol solution of a silane coupling agent KH-560 having a volume of 25% and a concentration of 6 wt% to the obtained graphene oxide aqueous dispersion, mixing and stirring the mixture, and then heat-retaining the mixture at a temperature of 65° C. for 10 hours; after the reaction is completed, naturally cooling the resultant components to room temperature, filtering the mixture, washing the filter cake with deionized water until it is neutral, and then drying the mixture to obtain the modified graphene oxide.

[0045] The preparation method of pretreated carbon nanotubes is as follows: carboxylated carbon nanotubes are ultrasonically dispersed in thionyl chloride at a solid-liquid ratio of 30 g / L, and then reacted at a temperature of 75°C for 20 hours; after the reaction is completed, the resulting components are naturally cooled to room temperature, and then filtered, washed and vacuum dried in sequence to obtain pretreated carbon nanotubes.

[0046] The preparation method of carboxylated carbon nanotubes is as follows: carbon nanotubes are added to a mixed acid solution at a dosage ratio of 20g / L, ultrasonically dispersed for 6 hours, and then allowed to stand and centrifuged; the precipitate is then washed with deionized water until it is neutral, and then vacuum dried to obtain carboxylated carbon nanotubes; wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.

[0047] Example 3

[0048] The preparation process of a bio-based polyurethane hot melt adhesive provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the bio-based polyurethane hot melt adhesive and the preparation method of the modified carbon nanotubes are not exactly the same. The specific composition of the bio-based polyurethane hot melt adhesive and the preparation method of the modified carbon nanotubes in this embodiment are as follows:

[0049] A bio-based polyurethane hot melt adhesive, comprising the following raw materials in parts by weight: 40 parts of bio-based polyester diol, 80 parts of bio-based polyether polyol, 35 parts of acrylic resin, 60 parts of isophorone diisocyanate, 5 parts of bisphenol A epoxy resin E-44, 5 parts of 1,4-butanediol, 0.6 parts of dibutyltin dilaurate, 1.0 parts of 3-aminopropyltriethoxysilane, 5 parts of modified carbon nanotubes, 4 parts of curing agent, 1.5 parts of ultraviolet absorber UV-1130, and 1.2 parts of antioxidant 1010;

[0050] Among them, the bio-based polyester diol is poly(1,3-propylene adipate) diol, and its relative molecular mass is 2000; the bio-based polyether polyol has a hydroxyl value of 60 mgKOH / g and a functionality of 3. It is prepared by ring-opening polymerization with propylene oxide using castor oil as an initiator and KOH as a catalyst.

[0051] The preparation method of modified carbon nanotubes comprises the following steps:

[0052] Step 1: adding pretreated carbon nanotubes to N,N-dimethylformamide at a ratio of 35 g / L, adding modified graphene oxide with a mass of 80% of the pretreated carbon nanotubes, ultrasonically dispersing for 2 hours, and then stirring at 85° C. for 15 hours; after the reaction is completed, reflux for 12 hours; cooling the reaction product to room temperature, and filtering, washing with water, and freeze-drying in sequence, and storing the obtained solid material for future use;

[0053] Step 2: The solid material is uniformly dispersed in a 95 wt% ethanol aqueous solution at a solid-liquid ratio of 80 g / L. A 30% volume concentration of tetrabutyl titanate ethanol dispersion with a volume ratio of 20% of the ethanol aqueous solution is added while stirring. The mixture is stirred until a large amount of white precipitate is generated. The resulting product components are allowed to stand, and then filtered and dried in sequence to obtain modified carbon nanotubes.

[0054] The preparation method of modified graphene oxide comprises the following steps: adding graphene oxide into deionized water at a solid-liquid ratio of 30 g / L, uniformly dispersing the graphene oxide by ultrasonication, and adjusting the pH to 5.0; then adding an ethanol solution of a silane coupling agent KH-560 having a volume of 30% and a concentration of 8 wt % to the obtained graphene oxide aqueous phase dispersion, mixing and stirring the mixture, and then heat-retaining the mixture at a temperature of 70° C. for 12 hours; after the reaction is completed, naturally cooling the resultant components to room temperature, filtering the resultant components, washing the filter cake with deionized water until the filter cake is neutral, and then drying the resultant components to obtain the modified graphene oxide.

[0055] The preparation method of pretreated carbon nanotubes is as follows: carboxylated carbon nanotubes are ultrasonically dispersed in thionyl chloride at a solid-liquid ratio of 50 g / L, and then reacted at a temperature of 85°C for 25 hours; after the reaction is completed, the resulting components are naturally cooled to room temperature, and then filtered, washed and vacuum dried in sequence to obtain pretreated carbon nanotubes.

[0056] The preparation method of carboxylated carbon nanotubes is as follows: carbon nanotubes are added to a mixed acid solution at a dosage ratio of 30g / L, ultrasonically dispersed for 8 hours, and then allowed to stand and centrifuged; the precipitate is then washed with deionized water until it is neutral, and then vacuum dried to obtain carboxylated carbon nanotubes; wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.

[0057] Comparative Example 1: The main difference between this comparative example and Example 1 is that in this comparative example, an equal amount of solid material is used to replace the modified carbon nanotubes.

[0058] Comparative Example 2: The main difference between this comparative example and Example 1 is that in this comparative example, an equal amount of carbon nanotubes is used instead of modified carbon nanotubes.

[0059] Performance Testing

[0060] The following performance tests were performed on the relevant properties of the bio-based polyurethane hot melt adhesive samples provided in Examples 1 to 3 and Comparative Examples 1 to 2:

[0061] 1. Shear strength test: Sample preparation and testing are carried out in accordance with GB / T7124-2008.

[0062] Bonding materials: PP&PC, ABS&PC (PP and other materials with low surface energy require corona or flame treatment).

[0063] Curing and curing: Curing and curing is carried out for 7 days at 23℃*65%.

[0064] Shear strength speed: V = 5mm / min.

[0065] 2. Tensile strength test: Sample preparation and testing shall be carried out in accordance with GB / T 528-2009.

[0066] Curing and curing: curing and curing for 7 days at 23℃*65%;

[0067] Tensile strength speed: V = 100 mm / min.

[0068] 3. Yellowing index test: The yellowing index of each group of bio-based polyurethane hot melt adhesive samples was tested according to the standard of HG / T 3862-2006 (the samples were irradiated on a xenon lamp aging instrument for 480 hours).

[0069] 4. Heat resistance test: The adhesive structure of Oxford cloth / aluminum sheet with high tear strength is placed in a 100℃ oven for aging for 10 days, and then the peel strength is tested in a constant temperature tensile testing machine at 50℃. The test is passed if the peel strength is greater than 40N / 25mm and failed if the peel strength is less than 40N / 25mm.

[0070] And record the test data in the following table:

[0071]

[0072] Comparing and analyzing the relevant data in the table shows that the bio-based polyurethane hot-melt adhesive prepared by the present invention not only has good bonding properties, but also excellent mechanical properties and aging resistance, effectively extending its service life while also ensuring its quality. This demonstrates that the bio-based polyurethane hot-melt adhesive and preparation process provided by the present invention have broader market prospects and are more suitable for promotion.

[0073] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0074] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A bio-based polyurethane hot melt adhesive, characterized in that: The invention is composed of the following raw materials in parts by weight: 30 to 40 parts of bio-based polyester diol, 60 to 80 parts of bio-based polyether polyol, 25 to 35 parts of acrylic resin, 40 to 60 parts of isophorone diisocyanate, 3 to 5 parts of bisphenol A epoxy resin E-44, 3 to 5 parts of 1,4-butanediol, 0.2 to 0.6 parts of dibutyltin dilaurate, 0.6 to 1.0 parts of 3-aminopropyltriethoxysilane, 3 to 5 parts of modified carbon nanotubes, 2 to 4 parts of curing agent, 1 to 1.5 parts of ultraviolet absorber and 0.8 to 1.2 parts of antioxidant.

2. The bio-based polyurethane hot melt adhesive according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: Step 1: adding pretreated carbon nanotubes to N,N-dimethylformamide at a ratio of 15 to 35 g / L, adding modified graphene oxide with a mass of 50 to 80% of the pretreated carbon nanotubes, ultrasonically dispersing for 1 to 2 hours, and then stirring at a temperature of 75 to 85° C. for 10 to 15 hours; after the reaction is completed, reflux reaction for 8 to 12 hours; cooling the reaction product to room temperature, and filtering, washing with water, and freeze-drying in sequence, and storing the obtained solid material for future use; Step 2: The solid material is uniformly dispersed in a 90-95 wt% ethanol aqueous solution at a solid-liquid ratio of 30-80 g / L. A tetrabutyl titanate ethanol dispersion having a volume of 10-20% of the ethanol aqueous solution and a volume concentration of 30-50% is added while stirring. The mixture is stirred until a large amount of white precipitate is generated. The resulting product components are allowed to stand, and then filtered and dried in sequence to obtain modified carbon nanotubes.

3. The bio-based polyurethane hot melt adhesive according to claim 2, characterized in that: The modified graphene oxide preparation method comprises the following steps: adding graphene oxide to deionized water at a solid-liquid ratio of 10 to 30 g / L, uniformly dispersing the graphene oxide by ultrasonication, and adjusting the pH to 4.5 to 5.0; then adding an ethanol solution of a silane coupling agent KH-560 having a volume of 20 to 30% and a concentration of 5 to 8 wt% to the obtained graphene oxide aqueous dispersion; mixing and stirring the mixture uniformly; and then heat-retaining the mixture at a temperature of 60 to 70° C. for 8 to 12 hours; and after the reaction is completed, naturally cooling the resultant components to room temperature, filtering the mixture, washing the filter cake with deionized water until it is neutral, and then drying the mixture to obtain the modified graphene oxide.

4. The bio-based polyurethane hot melt adhesive according to claim 2, characterized in that: The preparation method of the pretreated carbon nanotubes comprises: ultrasonically dispersing carboxylated carbon nanotubes in thionyl chloride at a solid-liquid ratio of 20 to 50 g / L, and then reacting at a temperature of 65 to 85° C. for 15 to 25 hours; after the reaction is completed, naturally cooling the resulting components to room temperature, and then filtering, washing, and vacuum drying in sequence to obtain the pretreated carbon nanotubes.

5. The bio-based polyurethane hot melt adhesive according to claim 4, characterized in that: The preparation method of the carboxylated carbon nanotubes comprises: adding carbon nanotubes in a mixed acid solution at a dosage ratio of 10 to 30 g / L, ultrasonically dispersing for 5 to 8 hours, and then sequentially standing and centrifuging; then washing the precipitate with deionized water until it becomes neutral, and then vacuum drying to obtain the carboxylated carbon nanotubes; wherein the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:

1.

6. The bio-based polyurethane hot melt adhesive according to claim 1, characterized in that: The bio-based polyester diol is poly(1,3-propylene adipate) diol, and its relative molecular mass is 1000-2000.

7. The bio-based polyurethane hot melt adhesive according to claim 1, characterized in that: The bio-based polyether polyol has a hydroxyl value of 55 to 60 mgKOH / g and a functionality of 3. It is prepared by ring-opening polymerization with propylene oxide using castor oil as an initiator and KOH as a catalyst.

8. The bio-based polyurethane hot melt adhesive according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1076, antioxidant 1035, antioxidant 245, and antioxidant 1010.

9. The bio-based polyurethane hot melt adhesive according to claim 1, characterized in that: The ultraviolet absorber is selected from any one of ultraviolet absorber UV-327, ultraviolet absorber UV-531, and ultraviolet absorber UV-1130.

10. A process for preparing a bio-based polyurethane hot melt adhesive according to any one of claims 1 to 9, characterized in that: The steps include: The first step is to put bio-based polyester diol, bio-based polyether polyol, acrylic resin and 1,4-butanediol into a reactor, raise the reactor temperature to 110-130°C, mix and stir evenly, and then dehydrate under vacuum conditions for 2-3 hours; after dehydration, cool to 50-70°C, then add isophorone diisocyanate under nitrogen protection, mix and stir evenly, and then keep stirring at 110-130°C for 2-3 hours; Step 2: After the reaction is completed, add dibutyltin dilaurate under the protection of nitrogen, evenly disperse it, and then keep it warm at 90-120°C for 40-60 minutes. After the reaction is completed, add the remaining raw materials into the reactor, keep it warm and stir for 50-80 minutes, and then degas for 10-20 minutes. After filtering, discharging, and vacuum sealing packaging, the bio-based polyurethane hot melt adhesive is obtained.

Citation Information

Patent Citations

  • Bio-based reactive polyurethane hot melt adhesive and preparation method thereof

    CN113736416A

Cited By

  • Silicon-free defoaming agent for oil and gas fields and preparation method of silicon-free defoaming agent

    CN121338401A

  • Modified waterborne polyurethane adhesive and preparation method thereof

    CN121406281A